PENGEMBANGAN ASESMEN DIAGNOSTIK PADA MATERI MENJAHIT BLAZER SMK NEGERI 2 TUBAN - Putriani, Puput; Ma'rifatun Nashikhah; Marniati Marniati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The diagnostic assessment sheet in this study was administered before the learning process began, aiming to assist teachers in identifying students’ strengths and weaknesses so that learning activities could be designed according to students’ individual needs. The assessment sheet consisted of both cognitive and non- cognitive components related to blazer sewing material. This research employed the Research and Development (R&D) method, conducted at SMK Negeri 2 Tuban, involving 24 students from Class 12 DPB 2 as research subjects. The results of the diagnostic assessment development on blazer sewing material at SMK Negeri 2 Tuban are as follows : 1) Validity results from experts indicated a “Very Valid” category with an average score of 91.4%, based on evaluations by assessment and language experts. The assessment experts gave a score of 89.5% (“Very Valid”), while the language experts gave 93.5% (“Very Valid”) 2) Student responses showed an average score of 70.1%, categorized as “Positive.” 3) Learning outcomes demonstrated an improvement in classical completeness by 21% (from 62.5% to 83%).